Impact of dietary digestible aromatic amino acid levels and stachyose on growth, nutrient utilization, and cecal odorous compounds in broiler chickens - Meiye Fu; Xiaoliang Zhou; Dafei Yin; Haiying Liu; Xin Zhu; Guiqin Yang (Poultry Science, 2024)
ABSTRACT: This study evaluated the impact of dietary digestible aromatic amino acid (DAAA) levels and stachyose on growth, nutrient utilization and cecal odorous compounds in broiler chickens. A 3×2 two-factor factorial design: Three dietary DAAA levels (1.40, 1.54, 1.68%) supplemented with either 5 g/kg of stachyose or without any stachyose were used to create 6 experimental diets. Each diet was fed to 6 replicates of 10 birds from d 22 to 42. Findings revealed that broilers receiving a diet with 1.54% DAAA levels supplemented with 5 g/kg stachyose exhibited a significant boost in average daily gain and improved utilization of crude protein, ether extract, tryptophan, and methionine compared to other diet treatments (P < 0.05). As the dietary DAAA levels increased, there was a significant rise in the concentrations of indole, skatole, p-methylphenol, and butyric acid in the cecum of broilers (P < 0.05). The addition of stachyose to diets reduced concentrations of indole, skatole, phenol, p-methylphenol, acetic acid and propionic acid in the cecum (P < 0.05). The lowest concentrations of indole, phenol, p-methylphenol, volatile fatty acids and pH in cecum of broilers were observed in the treatment which diet DAAA level was 1.40% with stachyose (P < 0.05). In conclusion, dietary DAAA levels and stachyose had significant interactions on the growth, main nutrient utilization and cecal odorous compounds in broilers. The dietary DAAA level was 1.54% with 5 g/kg of stachyose can improve the growth performance, nutrient utilization. However, the dietary DAAA level was 1.40% with stachyose was more beneficial to decrease the cecal odor compound composition in broilers.